2018
DOI: 10.14349/rlp.2018.v50.n2.4
|View full text |Cite
|
Sign up to set email alerts
|

Resolución de problemas interpersonales en niños en exclusión social: Valoración de un programa de entrenamiento

Abstract: Resumen La exclusión social es uno de los mayores desafíos de las sociedades modernas especialmente para una de las poblaciones más afectadas: la infancia. Crecer en ambientes desfavorecidos tiene un impacto negativo en la salud, la educación o el desarrollo cognitivo, emocional y social. Una de las áreas especialmente afectadas en estos niños es la competencia social, entendida como la habilidad del sujeto para enfrentarse a situaciones sociales problemáticas de forma exitosa. Este trabajo se centra en las ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…However, results only showed statistically significant between-group differences in two EF measures (working memory index and letters-numbers) and in one IS measure (Questionnaire of Interpersonal Conflict Resolution Solutions score). Therefore, our results seem to go in line with previous studies that found EF and IS difficulties in children, preadolescents, and adolescents exposed to risk situations, such as poverty, low socioeconomic status, or high-risk families (Arán-Filippetti, 2013; Dickerson & Popli, 2016; Ison & Morelato, 2002; Maddio & Greco, 2010; Martin et al, 2012; Mata, Gómez-Pérez, Molinero, & Calero, 2017; Raver et al, 2013; Rhoades et al, 2011; Sarsour et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, results only showed statistically significant between-group differences in two EF measures (working memory index and letters-numbers) and in one IS measure (Questionnaire of Interpersonal Conflict Resolution Solutions score). Therefore, our results seem to go in line with previous studies that found EF and IS difficulties in children, preadolescents, and adolescents exposed to risk situations, such as poverty, low socioeconomic status, or high-risk families (Arán-Filippetti, 2013; Dickerson & Popli, 2016; Ison & Morelato, 2002; Maddio & Greco, 2010; Martin et al, 2012; Mata, Gómez-Pérez, Molinero, & Calero, 2017; Raver et al, 2013; Rhoades et al, 2011; Sarsour et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…These favorable results concur with results of other studies where significant improvements were found in relation to EF, behavior problems, social adjustment, and academic success (Arán-Filippetti, Richaud de Minzi, 2011; Durlak et al, 2011; Ghiglione et al, 2011; Menting et al, 2013; Neville et al, 2013; Segretin et al, 2014). In addition, our results offer new evidence of the benefits of applying mediated learning methodology to train EF and IS jointly, going one step further than previous programs that used this methodology to address a single type of skill (Bonete et al, 2016; Calero, Gómez-Pérez, & Mata, 2017; Gómez-Pérez et al, 2014; Mata, Gómez-Pérez, & Calero, 2017).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It has usually been assumed that public schools have higher vulnerability, as can be seen in studies comparing public, subsidized, and private educational institutions 8 . However, although in the present study the latter 2 are simply classified under low vulnerability, it is important to mention that several public schools were classified under low vulnerability.…”
Section: Discussionmentioning
confidence: 72%
“…A better understanding of how these problems manifest can allow for more focused interventions that make more sense for educational communities. For Mata et al, 8 social exclusion is a reality experienced by many children that affects the development of their physical and emotional health, among others, highlighting the importance of intervention with training programs seeking interpersonal solution.…”
Section: Introductionmentioning
confidence: 99%